Incidence, risk factors and outcomes of healthcare associated urinary tract infection in icu Hospital Sungai Buloh - Omar, Mohammad Faisol Hamdi (2013)
Healthcare associated infection (HCAI) is a localized or systemic condition due to infection that occurs 48 hours or more after patient being admitted to the hospital. HCAI is considered as a serious event in clinical settings and most of the time is preventable. Healthcare associated urinary tract infection (HCA-UTI) is the commonest type of HCAI. The risk factors that contribute to the development of HCA-UTI include the insertion of indwelling urinary catheter, duration of catheterization, systemic antibiotics, female gender, age > 65 years old, serum creatinine > 2 mg/dL, diabetes mellitus and lack of aseptic techniques during insertion of urinary catheter. The clinical diagnosis might be difficult in view of the lack of signs and symptoms presented by patient with HCA-UTI. Laboratory analysis of the urine specimen may help in determining the diagnosis of HCA-UTI. The aim of this study is to determine the incidence, risk factors and outcomes of HCA-UTI in ICU Hospital Sungai Buloh. This is a prospective cohort study which was conducted in ICU Hospital Sungai Buloh for duration of 6 months (September 2012 - February 2013). Urine specimens from participants were collected after 48 hours of admission to ICU and monitored until they discharged from ICU. The risk factors of each participant were studied and outcomes were observed. Among 677 admissions to ICU in September 2012 - February 2013, only 220 (32.5%) met the inclusion criteria. Only 21 patients had HCA-UTI thus the incidence of HCA-UTI in ICU Hospital Sungai Buloh was 9.5% (95% Cl 5.6, 13.4). The associated risk factors were analyzed using Multiple Logistic Regression model and showed only length of ICU stay (RR 1.07, 95%CI 1.03, 1.13, p<0.001) was the significant risk factor to develop HCA-UTI in this study. The commonest microorganism isolated were Candida albicans (23.8%) and Pseudomonas aeruginosa (23.8%). Majority of patients with HCA-UTI were discharged stable and mortality was 33.3% overall. HCA-UTI is a condition that usually overlooked by healthcare personnel. Prevention of the occurrence with proper measures and optimize catheter care is important to minimize the rate of HCA-UTI in hospitals.